2021
DOI: 10.1111/phn.12910
|View full text |Cite
|
Sign up to set email alerts
|

The experience of individuals placed in quarantine: A systematic review, meta‐summary, and meta‐synthesis

Abstract: Objective To summarize the experience of individuals placed in quarantine during an outbreak. Design A meta‐summary and a meta‐synthesis based upon a systematic review of qualitative studies. Sample The Cumulative Index of Nursing and Allied Health Literature, MEDLINE, and Scopus databases were all searched up to April 2020. Measurements The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses guideli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 44 publications
2
9
0
Order By: Relevance
“…Our findings validate previous systematic reviews concerning the physical and psychological ordeals faced by infected individuals (Basso et al, 2021). The emotional experiences reported here align with previous studies, revealing a wide spectrum of emotions, including anxiety, shock, fear, sadness, and anger (Bian et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings validate previous systematic reviews concerning the physical and psychological ordeals faced by infected individuals (Basso et al, 2021). The emotional experiences reported here align with previous studies, revealing a wide spectrum of emotions, including anxiety, shock, fear, sadness, and anger (Bian et al, 2022).…”
Section: Discussionsupporting
confidence: 92%
“…The previous systematic review summarized the negative psychological impact of the quarantine on individuals (Basso et al, 2021). Findings from our study further added to the literature on coping strategies during older women's home‐quarantine period.…”
Section: Discussionmentioning
confidence: 99%
“…The previous systematic review summarized the negative psychological impact of the quarantine on individuals (Basso et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to increased infection risks, rates of quarantine have been significantly higher in hospitals HCWs compared to the general public (Kumar et al, 2020) and have been found to be associated with PTSD symptoms (Brooks et al, 2020; Brophy et al, 2020; Carmassi et al, 2020). While an effective measure to reduce nosocomial outbreaks of COVID-19 in hospitals (Grzelakowska and Kryś, 2021; Huang et al, 2021), studies have demonstrated that quarantine procedures can have severe psychological impact due to feelings of threat, restrain and social isolation (Basso et al, 2021; Brooks et al, 2020; Gómez-Durán et al, 2020), which were likely intensified as hospital HCWs face repeated quarantine and its’ consequences due to their work in hospitals. Another contributing factor could be the social stigma and social rejection (Ding et al, 2021; Gómez-Durán et al, 2020; Schubert et al, 2021; Yuan et al, 2021b) faced by these professional groups due to their work, which have been found to increase experiences of PTSD symptoms (Yuan et al, 2021a).…”
Section: Discussionmentioning
confidence: 99%